Laminate and packaging material
Patent Information
- Application Number
- JP2023126960
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-14
AI Technical Summary
【0008】 本発明によれば、アルミニウム箔やアルミニウム蒸着膜等を有さずに高いガスバリア性を有する、包装材料に適用可能なガスバリア性積層体を提供できる。
Smart Images

Figure 2025022416000001 
Figure 2025022416000002 
Figure 2025022416000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate and a packaging material having gas barrier properties. [Background technology]
[0002] Gas barrier materials are used in various fields to prevent the intrusion of gases such as moisture and oxygen from the outside air. For example, packaging materials used for packaging food and beverages are required to protect the contents from various distribution processes, storage such as refrigeration, heat sterilization, and other processes, and to have oxygen barrier properties to prevent the intrusion of oxygen from the outside in order to suppress oxidation for the purpose of long-term food storage, carbon dioxide barrier properties, and barrier properties against various aroma components, etc. In addition, in electronic devices such as solar cells, various displays such as liquid crystal, organic or inorganic electroluminescence (hereinafter referred to as "EL"), and electronic paper, glass substrates are generally used as sealing materials to protect the internal structure and block oxygen and water vapor from the outside, but the use of transparent gas barrier films using plastic films as a base material is being considered for the purpose of providing products that are thinner, lighter, or more flexible (see, for example, Patent Documents 1 and 2).
[0003] Recently, packaging materials and sealants are required to be recyclable when they are disposed of. Conventionally, the most common method for imparting gas barrier properties has been to use aluminum foil or aluminum vapor deposition film as part of the composition, but since aluminum reduces recyclability, there is a demand for gas barrier materials that do not use aluminum. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2005-077553 A [Patent Document 2] JP 2010-253861 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a gas barrier laminate that has high gas barrier properties without using an aluminum foil, an aluminum vapor-deposited film, or the like, and that can be used as a packaging material. [Means for solving the problem]
[0006] That is, the present invention provides a laminate including a first substrate and a gas barrier resin layer, The present invention provides a laminate, wherein the gas barrier resin layer is (A1) or (A2). (1) Water-soluble polymer with hydroxyl groups and Si(OR 1 )4, or R 2 Si(OR 3 )3(However, OR 1 and OR 3 represents a hydrolyzable group, R 2 represents an organic functional group), or one or more hydrolyzates of the silicon compounds. (2) Gas barrier resin layer (A2) containing a heteroatom compound having dehydration condensation properties and a polymer having a carboxyl group
[0007] The present invention also provides a packaging material comprising the laminate. Effect of the Invention
[0008] According to the present invention, it is possible to provide a gas barrier laminate that has high gas barrier properties without using an aluminum foil, an aluminum vapor-deposited film, or the like, and that can be used as a packaging material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In this specification, the symbol "to" means a value equal to or greater than the value before the symbol "to" and equal to or less than the value after the symbol "to".
[0010] (First substrate) The first substrate used in the present invention is not particularly limited, and examples thereof include polyolefin films such as polyethylene terephthalate (PET) film, polystyrene film, polyamide film, nylon film, polyacrylonitrile film, polyethylene film (OPE: biaxially oriented polyethylene film, LLDPE: low density polyethylene film, HDPE: high density polyethylene film) and polypropylene film (CPP: non-oriented polypropylene film, OPP: biaxially oriented polypropylene film), polyvinyl alcohol film, ethylene-vinyl alcohol copolymer film, cellophane, and the like.
[0011] In addition, films having inorganic vapor deposition layers of metal oxides such as silica and alumina can also be used. Specific examples include OPE films, OPP films, PET films, and nylon films having a silica vapor deposition layer, and OPE films, OPP films, PET films, and nylon films having an alumina vapor deposition layer.
[0012] When considering mono-material packaging, a film made of a thermoplastic resin mainly composed of an olefin resin can be used as the substrate. Specific examples of olefin resins include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear (linear) low-density polyethylene, polypropylene, ethylene-propylene copolymers, α-olefin polymers, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ethylene-acrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-ethyl acrylate copolymers, cyclic olefin resins, ionomer resins, and polymethylpentene; and modified olefin resins obtained by modifying olefin resins with acrylic acid, methacrylic acid, maleic anhydride, fumaric acid, and other unsaturated carboxylic acids.
[0013] It is also preferable to use a film formed from a material containing a biomass-derived component as the film substrate. Biomass films are sold by various companies, and for example, sheets such as those listed in the list of biomass certified products listed in the Japan Organics Resources Association can be used.
[0014] Specifically, a well-known film is made from biomass-derived ethylene glycol. Biomass-derived ethylene glycol is made from ethanol (biomass ethanol) produced from biomass. For example, biomass-derived ethylene glycol can be obtained by a method of producing ethylene glycol from biomass ethanol via ethylene oxide using a conventionally known method. Commercially available biomass ethylene glycol may also be used, and for example, biomass ethylene glycol commercially available from India Glycoal Limited can be suitably used.
[0015] Alternatively, products using biomass raw materials classified by the degree of biomass plastic as stipulated by ISO16620 or ASTM D6866 are also on the market. Radioactive carbon-14C exists in the atmosphere at a ratio of 1 in 1012 particles, and this ratio does not change even with atmospheric carbon dioxide, so this ratio does not change even in plants that fix this carbon dioxide through photosynthesis. For this reason, the carbon in plant-derived resins contains radioactive carbon-14C. In contrast, the carbon in fossil fuel-derived resins contains almost no radioactive carbon-14C. Therefore, by measuring the concentration of radioactive carbon-14C in the resin with an accelerator mass spectrometer, the proportion of plant-derived resin in the resin, i.e., the degree of biomass plastic, can be determined. Examples of plant-derived low-density polyethylene, which is a biomass plastic having a biomass plastic content of 80% or more, preferably 90% or more as specified by ISO16620 or ASTM D6866, include Braskem products under the trade names "SBC818", "SPB608", "SBF0323HC", "STN7006", "SEB853", and "SPB681", and films using these as raw materials can be preferably used.
[0016] For example, as an alternative to conventional polyolefin films using petroleum-based raw materials, biomass polyolefin films such as biomass polyethylene films and biomass polyethylene-polypropylene films, which contain polyethylene resins made from biomass-derived ethylene glycol, are also known. The polyethylene resin is not particularly limited except that ethylene glycol derived from biomass is used as part of the raw material. Examples of the polyethylene resin include ethylene homopolymers and copolymers of ethylene and α-olefins with ethylene as the main component (ethylene-α-olefin copolymers containing 90% by mass or more of ethylene units). These may be used alone or in combination of two or more. The α-olefin constituting the copolymer of ethylene and α-olefin is not particularly limited, and examples thereof include α-olefins having 4 to 8 carbon atoms, such as 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene. Known polyethylene resins, such as low-density polyethylene resin, medium-density polyethylene resin, and linear low-density polyethylene resin, can be used. Among these, from the viewpoint of making it more difficult for damage such as holes or tears to occur even when films are rubbed against each other, linear low-density polyethylene resin (LLDPE) (a copolymer of ethylene and 1-hexene, or a copolymer of ethylene and 1-octene) is preferred, and linear low-density polyethylene resin having a density of 0.910 to 0.925 g / cm3 is more preferred.
[0017] The biomass film may be a laminate of a plurality of biomass films, or may be a laminate of a conventional petroleum-based film and a biomass film.
[0018] The substrate may be one that has been subjected to any surface treatment, such as a physical treatment such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas or nitrogen gas, glow discharge treatment, or flame treatment, or a chemical treatment such as an oxidation treatment using a chemical agent, or other treatment.
[0019] The substrate can be produced from the above-mentioned resin by a conventionally known film-forming method such as an extrusion method, a cast molding method, a T-die method, a cutting method, an inflation method, etc. It may be an unstretched film, or may be a film stretched uniaxially or biaxially using a tenter method, a tubular method, etc., from the viewpoint of the strength, dimensional stability, and heat resistance of the film (1).
[0020] The substrate may contain additives as necessary. Specifically, plastic compounding agents and additives such as elastomers, lubricants, crosslinking agents, antioxidants, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, and pigments may be added for the purpose of improving or modifying processability, heat resistance, weather resistance, mechanical properties, dimensional stability, antioxidant properties, slipperiness, mold releasability, flame retardancy, antifungal properties, electrical properties, strength, etc. The amount of additives added is adjusted within a range that does not affect other performance properties or recyclability.
[0021] The thickness of the substrate is not particularly limited, and may be appropriately selected from the range of 0.1 to 300 μm from the viewpoint of moldability and transparency. The thickness is preferably in the range of 0.3 to 100 μm. If the thickness is less than 0.1 μm, the strength is insufficient, and if it exceeds 300 μm, the rigidity is too high, which may make processing difficult.
[0022] From the viewpoint of recycling, it is preferable that the layer structure is as simple as possible, but from the viewpoint of distribution of the packaging material, printing is often required to display the contents of the packaging material or a description or name of the product. The substrate is often printed as well.
[0023] (Printing layer) The printing layer is a layer on which characters, figures, symbols, and other desired patterns are printed. There is no particular limitation on the printing method or printing ink, and any known printing method or printing ink can be used. Printing inks using gravure printing, flexographic printing, lithographic offset printing, inkjet recording printing, and the like are often used for the film used as the substrate. Printing inks that combine these printing methods with methods of curing with active energy rays such as ultraviolet rays (UV), LEDs, and electron beams (EB), or methods of curing with heat, and the like, are also used. In addition, depending on the solvent used, they may be referred to as water-based inks or organic solvent-based inks.
[0024] Specific examples include gravure printing ink and flexographic printing ink (in some industries, gravure printing ink and flexographic printing ink are referred to as liquid ink), ultraviolet-curable ink for lithographic offset printing, electron-beam-curable ink for lithographic offset printing, ultraviolet-curable ink for inkjet recording and printing, and electron-beam-curable ink for inkjet recording and printing.
[0025] The position where the printed layer printed using these inks is provided is arbitrary, and it may be provided on the first substrate, or a substrate on which a separate printed layer is provided may be one of the components of the laminate of the present invention, and the position is arbitrary. The ink may contain a resin, a colorant, and a solvent as essential components, or it may be a so-called clear ink that contains a resin and a solvent but does not substantially contain a colorant. Below, we will explain the liquid inks that are most commonly used for printing on film.
[0026] The resin used in the liquid ink is not particularly limited, and examples thereof include acrylic resin, polyester resin, styrene resin, styrene-maleic acid resin, maleic acid resin, polyamide resin, polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, vinyl chloride-acrylic copolymer resin, ethylene-vinyl acetate copolymer resin, vinyl acetate resin, polyvinyl chloride resin, chlorinated polypropylene resin, cellulose-based resin, epoxy resin, alkyd resin, rosin-based resin, rosin-modified maleic acid resin, ketone resin, cyclized rubber, chlorinated rubber, butyral, petroleum resin, etc., and one or more of them can be used in combination. Preferably, at least one or two or more selected from polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, and cellulose-based resin are used.
[0027] Colorants used in liquid inks include inorganic pigments such as titanium oxide, red iron oxide, antimony red, cadmium red, cadmium yellow, cobalt blue, Prussian blue, ultramarine, carbon black, and graphite; organic pigments such as soluble azo pigments, insoluble azo pigments, azo lake pigments, condensed azo pigments, copper phthalocyanine pigments, and condensed polycyclic pigments; and extender pigments such as calcium carbonate, kaolin clay, barium sulfate, aluminum hydroxide, and talc.
[0028] Liquid inks for film printing are often organic solvent-based inks. The organic solvents used preferably do not contain aromatic hydrocarbon organic solvents. More specifically, examples of the organic solvents include alcohol-based organic solvents such as methanol, ethanol, n-propanol, isopropanol, and butanol; ketone-based organic solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ester-based organic solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate; aliphatic hydrocarbon-based organic solvents such as n-hexane, n-heptane, and n-octane; and alicyclic hydrocarbon-based organic solvents such as cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, and cyclooctane. These may be used alone or in combination of two or more.
[0029] (Gas barrier resin layer) The gas barrier resin layer used in the present invention is characterized by being (A1) or (A2). (1) Water-soluble polymer with hydroxyl groups and Si(OR 1 )4, or R 2 Si(OR 3 )3(However, OR 1 and OR 3 represents a hydrolyzable group, R 2 represents an organic functional group), or one or more hydrolyzates of the silicon compounds. (2) Gas barrier resin layer (A2) containing a heteroatom compound having dehydration condensation properties and a polymer having a carboxyl group
[0030] (Gas barrier resin layer (A1)) The gas barrier resin layer (A1) used in the present invention contains a water-soluble polymer having a hydroxyl group. Examples of water-soluble polymers having a hydroxyl group include vinyl alcohol polymers, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, etc. Among them, it is preferable to use vinyl alcohol polymers because they can provide good gas barrier properties.
[0031] The vinyl alcohol polymer may be a hydrolyzate of a homopolymer or copolymer of a vinyl ester (a1) obtained by a known, commonly used method, or a reaction product of a hydrolyzate of a homopolymer or copolymer of a vinyl ester (a1) with an aldehyde obtained by a known, commonly used method.
[0032] Examples of the vinyl ester (a1) include vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, vinyl caproate, vinyl caprylate, vinyl laurate, vinyl palmitate, vinyl stearate, vinyl oleate, vinyl benzoate, etc., and one or more of these can be used in combination. It is preferable to use vinyl acetate.
[0033] Examples of the polymerizable compound (a2) that can be copolymerized with the vinyl ester (a1) include ethylene, propene, 1-butene, isobutylene, 1,3-butadiene, isopropenyl acetate, 2-propenyl acetate, styrene, α-methylstyrene, vinyl chloride, acrylonitrile, maleic anhydride, methyl acrylate, methyl methacrylate, N-vinyl-N-methylformamide, vinylacetamide, N-vinylformamide, N-(hydroxymethyl)-N-vinylformamide hydroxyethyl acrylate, methyl vinyl ketone, and diacetone acrylamide, and can be used alone or in combination of two or more. Among these, it is preferable to use ethylene, isopropenyl acetate, and 2-propenyl acetate.
[0034] When the vinyl ester (a1) and the polymerizable compound (a2) are used in combination, the amounts of these compounds used can be appropriately adjusted. From the viewpoint of gas barrier properties, however, the amount of the polymerizable compound (a2) blended is preferably kept at 60 mol % or less, more preferably 25 mol % or less, of the total amount of the vinyl ester (a1) and the polymerizable compound (a2).
[0035] The degree of polymerization of the vinyl ester polymer, which is a precursor of the vinyl alcohol polymer, is not particularly limited, but is, for example, 500 to 10,000, more preferably 800 to 6,000, and more preferably 1,000 to 3,000. This makes it possible to provide a coating agent with an excellent balance between gas barrier properties and coatability.
[0036] Aldehydes used for acetalization include aliphatic aldehydes such as formaldehyde, acetaldehyde, propylaldehyde, butylaldehyde, octylaldehyde, and dodecylaldehyde; alicyclic aldehydes such as cyclohexanecarbaldehyde; aromatic aldehydes such as benzaldehyde, naphthaldehyde, anthraldehyde, phenylacetaldehyde, tolualdehyde, dimethylbenzaldehyde, cuminaldehyde, and benzylaldehyde; cyclohexene aldehyde, dimethylcyclohexene aldehyde, acrylonitrile, and the like; Examples of the aldehyde include unsaturated aldehydes such as chlorine; aldehydes having a heterocycle such as furfural and 5-methylfurfural; hemiacetals such as glucose and glucosamine; and aldehydes having an amino group such as 4-aminobutyraldehyde. In addition, aliphatic ketones such as 2-propanone, methyl ethyl ketone, 3-pentanone, and 2-hexanone; aliphatic alicyclic ketones such as cyclopentanone and cyclohexanone; and aromatic ketones such as acetophenone and benzophenone can be used alone or in combination of two or more.
[0037] As the acid catalyst used in the acetalization, conventionally known organic acids or inorganic acids such as acetic acid, paratoluenesulfonic acid, nitric acid, sulfuric acid, and hydrochloric acid can be used.
[0038] Suitable specific examples of vinyl alcohol-based polymers include polyvinyl alcohol, ethylene vinyl alcohol, polyvinyl butyral, etc. One type may be used alone, or two or more types may be used in combination. From the viewpoint of the balance between gas barrier properties and adhesion, it is more preferable to use either polyvinyl alcohol or ethylene vinyl alcohol, or both.
[0039] The gas barrier resin layer (A1) used in the present invention is made of Si(OR 1 )4, or R 2 Si(OR 3 )3(However, OR 1 and OR 3 represents a hydrolyzable group, R 2represents an organic functional group), or a hydrolyzate of the silicon compound. Examples of these silicon compounds or hydrolysates of the silicon compounds include tetraalkoxysilanes such as tetraethylsilicate (Si(OC2H5)4) (hereinafter sometimes referred to as TEOS) and tetramethylsilicate; trialkoxysilanes such as trimethoxymethylsilane, triethoxymethylsilane, trimethoxyvinylsilane; dialkoxysilanes such as dimethoxydimethylsilane, diethoxydimethylsilane; monoalkoxysilanes such as methoxytrimethylsilane, ethoxytrimethylsilane, or hydrolysates or partial hydrolysates thereof.
[0040] TEOS is preferred because it is relatively stable in an aqueous solvent after hydrolysis. 2 Si(OR 3 )3 contains R 2 is preferably a vinyl group, an epoxy group, an acryloyl group, a methacryloxy group, a ureido group, or an isocyanate group.
[0041] When the water-soluble polymer is a vinyl alcohol polymer, the ratio of the mass of the vinyl alcohol polymer to the mass of the total solid content of the mixed solution is preferably 20% by mass or more and 50% by mass or less, more preferably 25% by mass or more and 40% by mass or less. By containing 20% by mass or more of PVA, the flexibility of the coating film is maintained. Therefore, the coating film is easily formed. In addition, by containing 50% by mass or less of the vinyl alcohol polymer, it is possible to have sufficient barrier properties.
[0042] The gas barrier resin layer (A1) may contain other components in addition to the water-soluble polymer having a hydroxyl group, the silicon compound, or the hydrolysate of the silicon compound. Examples of other components include other water-soluble polymers (e.g., sodium polyacrylate, polyethylene oxide, polyvinylpyrrolidone, dextrin, chitosan, chitin, methylcellulose, hydroxyethylcellulose, etc.), fragrances, rust inhibitors, colorants, extenders, antifoaming agents, ultraviolet absorbers, fluorescent brighteners, liquid paraffins, bitter components (e.g., denatonium benzoate, etc.), etc.
[0043] The method for forming the gas barrier resin layer (A1) is not particularly limited and may be a known method. The easiest method is to coat the first substrate with a coating liquid (A1) (hereinafter, sometimes simply referred to as coating liquid (A1)) containing the water-soluble polymer having a hydroxyl group and one or more types of the silicon compound or hydrolysates of the silicon compound, by a known coating method to form a coating film. Examples of the coating method that can be used include spraying, spin coating, dipping, roll coating, blade coating, doctor roll, doctor blade, curtain coating, slit coating, screen printing, inkjet, dispensing, die coating, direct gravure, reverse gravure, flexography, knife coating, and dot coating.
[0044] (Water-based solvent) To facilitate application, the coating liquid (A1) preferably contains an optional aqueous solvent. As the aqueous solvent, water, water-soluble organic solvents that dissolve in water, etc. can be used. As the water, pure water such as ion-exchanged water, ultrafiltered water, reverse osmosis water, distilled water, etc., or ultrapure water can be used. From the viewpoint of long-term storage, it is preferable to use water that has been sterilized by ultraviolet irradiation or addition of hydrogen peroxide, etc., in order to prevent the growth of mold or bacteria.
[0045] Examples of water-soluble organic solvents include glycols such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, polyethylene glycol, and polypropylene glycol; diols such as butanediol, pentanediol, and hexanediol; glycol esters such as propylene glycol laurate; diethylene glycol ethers such as diethylene glycol monoethyl, diethylene glycol monobutyl, diethylene glycol monohexyl, and carbitol; glycol ethers such as propylene glycol ether, dipropylene glycol ether, and cellosolve including triethylene glycol ether; alcohols such as methanol, ethanol, isopropyl alcohol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, butyl alcohol, and pentyl alcohol; lactones such as sulfolane, esters, ketones, and γ-butyrolactone, lactams such as N-(2-hydroxyethyl)pyrrolidone, and various other solvents known as aqueous organic solvents, such as glycerin and its polyalkylene oxide adducts, can be mentioned. These aqueous organic solvents can be used alone or in combination of two or more.
[0046] The thickness of the gas barrier resin layer (A1) is preferably selected, for example, from the range of 0.05 μm or more and 30 μm or less.
[0047] (Gas barrier resin layer (A2)) The gas barrier resin layer (A2) used in the present invention contains a heteroatom compound having a dehydration condensation property and a polymer having a carboxyl group.
[0048] (Heteroatom Compounds with Dehydration Condensation Properties) The dehydration condensation heteroatom compound used in the present invention is a compound that causes dehydration condensation when it comes into contact with a compound having a hydroxyl group, and is a compound that has a heteroatom in its structure. Examples of the dehydration condensation heteroatom compound include phosphoric acid, sulfuric acid, and nitric acid. These phosphoric acid, sulfuric acid, and nitric acid may be used alone or in combination.
[0049] The amount of the dehydrating condensable heteroatom compound added is not particularly limited as long as the effects of the present invention can be obtained. However, it is preferable that the compound is contained in the gas barrier resin layer (A2) in an amount of 10 parts by mass or less, and it is particularly preferable that the compound is contained in an amount of 4 to 6 parts by mass, since this further improves the adhesion when the compound comes into contact with a compound having a hydroxyl group in the composition.
[0050] (Polymer having carboxyl group) The polymer having a carboxyl group used in the present invention is a polymer made from a polymerizable unsaturated monomer having a carboxyl group in its structure (hereinafter, "polymerizable unsaturated monomer" will be referred to as "monomer") as a polymerization raw material. Specific examples of monomers having a carboxyl group in their structure include (meth)acrylic acid and β-carboxyethyl (meth)acrylate, and (meth)acrylic acid is preferred. The carboxyl group in the present invention may also include a structure in which an H2O molecule has been lost from two molecules of carboxylic acid, such as carboxylic acid anhydride. In addition, in the present invention, "(meth)acrylic acid" refers to either or both of acrylic acid and methacrylic acid, and "(meth)acrylate" refers to either or both of acrylate and methacrylate.
[0051] The acid value of the polymer having a carboxyl group is not particularly limited within the range in which the effects of the present invention can be obtained, but an acid value of 50 to 800 mgKOH / g is preferable because the barrier performance is improved. Also, an acid value of 80 to 800 mgKOH / g is more preferable, and an acid value of 80 mgKOH / g or more sufficiently promotes ionic bonding to obtain high barrier performance.
[0052] (Acid value measurement method) The acid value is the amount of potassium hydroxide (mg) required to neutralize the acid content in 1 g of sample. Specifically, a weighed sample is dissolved in a suitable solvent in which the sample dissolves, for example, a solvent with a volume ratio of toluene / methanol = 70 / 30, and several drops of a 1% phenolphthalein alcohol solution are dropped into the solution, and a 0.1 mol / L potassium hydroxide alcohol solution is dropped into the solution to confirm the discoloration point. The acid value can be measured by the following calculation formula.
[0053] (Acid value measurement method-1) Acid value (mgKOH / g)=(V×F×5.61) / S V: Amount of 0.1 mol / L potassium hydroxide alcohol solution used (mL) F: Potency of 0.1 mol / L potassium hydroxide alcohol solution S: Amount of sample collected (g) 5.61: The amount of potassium hydroxide (mg) in 1 mL of 0.1 mol / L potassium hydroxide alcohol solution
[0054] If the sample is a resin solution, the resin acid value (mgKOH / g) can be calculated using the following formula.
[0055] Resin acid value (mgKOH / g) = Acid value of resin solution (mgKOH / g) / NV(%) x 100 NV: Non-volatile content (%)
[0056] In addition, when the solubility of the sample in an organic solvent is low and precipitation occurs, making the measurement difficult, the acid value can also be measured by the following method.
[0057] (Acid value measurement method-2) The acid value (mgKOH / g-resin) is a value calculated by the following formula using an FT-IR (JASCO Corporation, FT-IR4200) and the coefficient (f) obtained from a calibration curve prepared using a chloroform solution of maleic anhydride, the absorbance (I) of the stretching peak (1780 cm-1) of the anhydride ring of maleic anhydride in a maleic anhydride-modified polyolefin solution, and the absorbance (II) of the stretching peak (1720 cm-1) of the carbonyl group of maleic acid. Acid value (mg KOH / g-regin) = [(absorbance (I) x (f) x 2 x molecular weight of potassium hydroxide x 1000 (mg) + absorbance (II) x (f) x molecular weight of potassium hydroxide x 1000 (mg)) / molecular weight of maleic anhydride] Molecular weight of maleic anhydride: 98.06, Molecular weight of potassium hydroxide: 56.11
[0058] The molecular weight of the polymer having a carboxyl group used in the present invention is not particularly limited, but from the viewpoint of good coating film formability, a weight average molecular weight of 300 to 1,000,000 is preferred, and a weight average molecular weight of 500 to 500,000 is particularly preferred. The weight average molecular weight of the polymer having a carboxyl group used in the present invention can be calculated by measuring by gel permeation chromatography (GPC).
[0059] The polymer having a carboxyl group is not particularly limited in terms of its resin skeleton as long as the effects of the present invention can be obtained, and may be a homopolymer of a polymerizable unsaturated monomer having a carboxyl group, or a copolymer using a plurality of polymerizable unsaturated monomers having a carboxyl group. It may also be a copolymer of a polymerizable unsaturated monomer having a carboxyl group and another monomer copolymerizable therewith. The polymer having a carboxyl group used in the present invention is preferably one or more polymers selected from the group consisting of acrylic acid, methacrylic acid, maleic acid, and itaconic acid.
[0060] ((Meth)acrylic acid polymer) The (meth)acrylic acid polymer may be any polymer of a (meth)acrylic acid monomer, and examples of such polymers include polyethers such as ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylates, ethylene oxide-modified 4,4-dihydroxydiphenylsulfone di(meth)acrylate, and ethylene oxide-modified bisphenol A di(meth)acrylate, ethylene glycol diglycidyl di(meth)acrylate, and ethylene oxide-modified bisphenol A diglycidyl di(meth)acrylate.
[0061] (Carboxyl-containing vinyl polymer) Examples of the carboxyl group-containing vinyl polymer resin include polymers of polymerizable unsaturated monomers having a carboxyl group. Examples of the polymerizable unsaturated monomers having a carboxyl group include unsaturated carboxylic acids such as (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, crotonic acid, itaconic acid, maleic acid, and fumaric acid; Monoesters (half esters) of various unsaturated dicarboxylic acids, such as monomethyl itaconate, mono-n-butyl itaconate, monomethyl maleate, mono-n-butyl maleate, monomethyl fumarate, and mono-n-butyl fumarate, with saturated monohydric alcohols; Monovinyl esters of various saturated dicarboxylic acids, such as monovinyl adipate or monovinyl succinate; Examples of the monomers include addition reaction products between various saturated polycarboxylic anhydrides, such as succinic anhydride, glutaric anhydride, phthalic anhydride, or trimellitic anhydride, and various hydroxyl group-containing vinyl monomers; and further, various monomers obtained by addition reaction of various carboxyl group-containing monomers as described above with lactones.
[0062] Examples of the monomer copolymerizable with the polymerizable unsaturated monomer having a carboxyl group include the following.
[0063] (meth)acrylic acid esters having an alkyl group having 1 to 22 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, stearyl (meth)acrylate, octadecyl (meth)acrylate, and docosyl (meth)acrylate;
[0064] (Meth)acrylic acid esters having an alicyclic alkyl group such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and dicyclopentenyloxyethyl (meth)acrylate; (meth)acrylic acid esters having an aromatic ring such as benzoyloxyethyl (meth)acrylate, benzyl (meth)acrylate, phenylethyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate; hydroxyethyl (meth)acrylate; hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and glycerol (meth)acrylate; acrylic acid esters having a hydroxyalkyl group such as lactone-modified hydroxyethyl (meth)acrylate, polyethylene glycol (meth)acrylate, and polypropylene glycol (meth)acrylate;
[0065] unsaturated dicarboxylic acid esters such as dimethyl fumarate, diethyl fumarate, dibutyl fumarate, dimethyl itaconate, dibutyl itaconate, methyl ethyl fumarate, methyl butyl fumarate, and methyl ethyl itaconate; styrene derivatives such as styrene, α-methylstyrene, and chlorostyrene; diene compounds such as butadiene, isoprene, piperylene, and dimethylbutadiene; vinyl halides and vinylidene halides such as vinyl chloride and vinyl bromide; unsaturated ketones such as methyl vinyl ketone and butyl vinyl ketone; vinyl esters such as vinyl acetate and vinyl butyrate; vinyl ethers such as methyl vinyl ether and butyl vinyl ether; vinyl cyanides such as acrylonitrile, methacrylonitrile, and vinylidene cyanide; acrylamide and its alkyd-substituted amides; N-substituted maleimides such as N-phenylmaleimide and N-cyclohexylmaleimide;
[0066] Fluorine-containing α-olefins such as vinyl fluoride, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, bromotrifluoroethylene, pentafluoropropylene, and hexafluoropropylene; or (per)fluoroalkyl perfluorovinyl ethers having a (per)fluoroalkyl group of 1 to 18 carbon atoms such as trifluoromethyl trifluorovinyl ether, pentafluoroethyl trifluorovinyl ether, and heptafluoropropyl trifluorovinyl ether; 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoro Examples of the fluorine-containing ethylenically unsaturated monomers include (per)fluoroalkyl (meth)acrylates having a (per)fluoroalkyl group having 1 to 18 carbon atoms, such as pentyl (meth)acrylate, 1H,1H,2H,2H-heptadecafluorodecyl (meth)acrylate, and perfluoroethyloxyethyl (meth)acrylate; silyl group-containing (meth)acrylates such as γ-methacryloxypropyltrimethoxysilane; and N,N-dialkylaminoalkyl (meth)acrylates such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, and N,N-diethylaminopropyl (meth)acrylate.
[0067] The polymer having a carboxyl group is obtained by polymerization or copolymerization using a known method, and the polymerization form is not particularly limited. Also, it can be produced by addition polymerization in the presence of a catalyst (polymerization initiator), and may be any of random copolymers, block copolymers, graft copolymers, etc. Also, the copolymerization method can be any known polymerization method such as bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc.
[0068] The gas barrier resin layer (A2) may contain compounds other than the dehydration condensation heteroatom compound and the polymer having a carboxyl group within the range where the effects of the present invention can be obtained. Examples of these additional additives include alcohols such as methanol, ethanol, propanol, butanol, and hexanol, solvents such as ethylene glycol, propylene glycol, and glycerin, coupling agents, silane compounds, phosphoric acid compounds, organic fillers, inorganic fillers, stabilizers (antioxidants, heat stabilizers, ultraviolet absorbers, etc.), plasticizers, antistatic agents, lubricants, antiblocking agents, colorants, crystal nucleating agents, oxygen scavengers (compounds having oxygen scavenging function), and tackifiers.
[0069] The gas barrier resin layer (A2) can be formed in the same manner as the gas barrier resin layer (A1), and the easiest method is to coat the first substrate with a coating liquid (A2) (hereinafter sometimes simply referred to as coating liquid (A2)) containing a heteroatom compound having dehydration condensation properties and a polymer having a carboxyl group by a known coating method to form a coating film. In order to facilitate coating, it is preferable that the coating liquid (A2) contains any organic solvent.
[0070] Furthermore, the gas barrier resin layer (A2) preferably has a resin layer (A2-2) containing a polyvalent metal compound adjacent thereto. Here, "adjacent" means that there is at least a part where the resin layer (A) and the resin layer (A2-2) are in direct contact with each other.
[0071] The polyvalent metal compound contained in the resin layer (A2-2) is a divalent or higher metal compound, which is mixed with a water-soluble polymer or the like to form the resin layer (A2-2). Examples of such polyvalent metal compounds include zinc compounds, magnesium compounds, calcium compounds, manganese compounds, iron compounds, cobalt compounds, nickel compounds, and copper compounds, and zinc compounds, magnesium compounds, and calcium compounds are particularly preferred. These metal compounds may be used alone or in combination of two or more.
[0072] The polyvalent metal compound that may be used in the present invention is preferably an oxide, hydroxide, or carbonate of a divalent metal, or may be a mixture of these. As the divalent metal compound, zinc oxide, magnesium oxide, and calcium oxide are preferred, and zinc oxide and magnesium oxide are particularly preferred.
[0073] The polyvalent metal compound is preferably in the form of particles. More preferably, it is fine particles having an average particle size of 10 nm or more and 500 nm or less. Particularly preferably, it is fine particles having an average particle size of 20 nm to 300 nm. The average particle size here is measured using a dynamic light scattering type particle size distribution measuring device, for example, LB-500 (manufactured by Horiba, Ltd.).
[0074] The polyvalent metal compound is preferably contained in the resin layer (A2-2) containing a polyvalent metal compound in an amount of 40 to 90 parts by mass, and particularly preferably in an amount of 60 to 80 parts by mass, since this improves the gas barrier properties.
[0075] In addition to the polyvalent metal compound, a resin is added to the resin layer (A2-2) containing the polyvalent metal compound in order to stably coat the polyvalent metal compound.Specific examples of the resin include cellulose resins, ethyl cellulose resins, carboxymethyl cellulose resins, polyester resins, epoxy resins, acrylic resins, methacrylic resins, polyamide resins, polyether polyurethane polyol resins, polyester polyol resins, and polyurethane polyol resins.These resins may be used alone or in combination.Among them, ethyl cellulose resins, polyether polyurethane polyol resins, polyester polyol resins, and polyurethane polyol resins are preferred.
[0076] The resin is preferably contained in the resin layer (A2-2) containing a polyvalent metal compound in an amount of 10 to 60 parts by mass, and particularly preferably in an amount of 20 to 40 parts by mass, since this provides good coatability for the resin layer (A2-2).
[0077] Furthermore, it is also preferred that the gas barrier resin layer (A2) has adjacent thereto a layer (A2-3) containing a compound selected from the group consisting of aluminum oxide, silicon oxide and silicon nitride. In the present invention, the layer (A2-3) provided adjacent to the resin layer (A) is a layer formed by depositing a compound selected from the group consisting of aluminum oxide, silicon oxide, and silicon nitride by a process such as deposition, sputtering, CVD, etc. These (A2-3) layers may be formed on substrate films such as polyethylene terephthalate (PET) resin films, polypropylene (PP) resin films, polybutylene terephthalate (PBT) resin films, nylon (NY) resin films, and biomass films, and the substrate films may be films manufactured by various known processes such as biaxially stretched films, stretched films, and non-stretched films, or films that have been subjected to various surface treatments as necessary.
[0078] The gas barrier resin layer (A2) is appropriately selected depending on the application, but the coating amount after drying is preferably 0.01 to 100 g / m 2 is preferable, and 0.1 to 50 g / m 2 More preferably, 0.5 to 3 g / m 2 is particularly preferred.
[0079] (Second substrate) The laminate including the first substrate and the gas barrier resin layer can be attached to the second substrate using an adhesive. Alternatively, the second substrate can be formed on the laminate by extrusion. The second substrate may be the same as or different from the first substrate. When the laminate of the present invention is applied to a packaging material, the second substrate is assumed to be used as a sealant layer, and a polyolefin resin having heat sealability can be selected as the second substrate. Examples of the polymer include polyethylene resins such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), very low-density polyethylene (VLDPE), polypropylene (CPP), ethylene-propylene copolymers, and polymethylpentene; ethylene-vinyl acetate copolymers (EVA), ethylene-methyl methacrylate copolymers (EMMA), ethylene-ethyl acrylate copolymers (EEA), ethylene-methyl acrylate (EMA) copolymers, ethylene-ethyl acrylate-maleic anhydride copolymers (E-EA-MAH), ethylene-acrylic acid copolymers (EAA), and ethylene-methacrylic acid copolymers (EMAA); and further, ionomers of ethylene-acrylic acid copolymers and ionomers of ethylene-methacrylic acid copolymers. These may be used alone or in combination of two or more. When the second layer is a heat seal layer, its thickness can be appropriately adjusted depending on the purpose, but from the viewpoint of aroma retention and heat sealability, it is, for example, 1 μm to 10 μm, more preferably 3 μm to 10 μm.
[0080] (glue) The adhesive used when bonding the second layer to the laminate including the first substrate and the gas barrier resin layer may be any adhesive that can be used in a general-purpose lamination method. Examples of the lamination method include dry lamination, wet lamination, non-solvent lamination, and extrusion lamination. The adhesive becomes an adhesive layer after curing or drying.
[0081] The adhesive used in the dry lamination may be, for example, a one-component or two-component cured or non-cured vinyl, (meth)acrylic, polyamide, polyester, polyether, polyurethane, epoxy, rubber, or other solvent, water-based, or emulsion-based adhesive. A two-component cured adhesive made of a polyol and an isocyanate compound may be used as the two-component cured adhesive. The lamination adhesive may be applied by, for example, a direct gravure roll coating method, a gravure offset roll coating method, a kiss coating method, a reverse roll coating method, a Fountain method, a transfer roll coating method, or other methods. For example, the DIC Dry series manufactured by DIC Corporation may be preferably used.
[0082] Also, various adhesives can be used, and it is preferable to use a pressure-sensitive adhesive. Examples of the pressure-sensitive adhesive include rubber-based adhesives obtained by dissolving polyisobutylene rubber, butyl rubber, or a mixture thereof in an organic solvent such as benzene, toluene, xylene, or hexane, or those obtained by blending a tackifier such as abiethylene acid rosin ester, terpene-phenol copolymer, or terpene-indene copolymer with these rubber-based adhesives, or acrylic-based adhesives obtained by dissolving an acrylic copolymer having a glass transition point of -20°C or less, such as 2-ethylhexyl acrylate-n-butyl acrylate copolymer or 2-ethylhexyl acrylate-ethyl acrylate-methyl methacrylate copolymer, in an organic solvent.
[0083] The adhesive may be a functional adhesive. For example, an adhesive having gas barrier properties may be the oxygen barrier adhesive PASLIM series manufactured by DIC Corporation, which is a two-liquid reactive adhesive of polyester polyol and isocyanate compound. The gas barrier adhesive becomes a gas barrier adhesive layer after curing or drying. Use of a gas barrier adhesive is preferable because it is possible to further improve the gas barrier properties of the laminate of the present invention.
[0084] When the adhesive is a solvent-based adhesive, the adhesive is applied to one substrate using a roll such as a gravure roll, and the organic solvent is evaporated by heating in an oven or the like, and then the other substrate is laminated to obtain the laminate of the present invention. It is preferable to perform an aging treatment after lamination. The aging temperature is preferably room temperature to 80°C, and the aging time is preferably 12 to 240 hours.
[0085] When the adhesive is a solventless type, the aroma-retaining adhesive, which has been preheated to about 40°C to 100°C, is applied to one of the substrates using a roll such as a gravure roll, and the other substrate is immediately laminated to obtain the laminate of the present invention. It is preferable to carry out an aging treatment after lamination. The aging temperature is preferably room temperature to 70°C, and the aging time is preferably 6 to 240 hours.
[0086] The amount of adhesive to be applied is adjusted as appropriate. For example, in the case of a solvent-based adhesive, the solid content is 1 g / m 2 More than 10g / m 2 Less than 1 g / m 2 More than 5g / m 2 Adjust the amount of adhesive applied as follows: For solvent-free adhesive, the amount of adhesive applied is, for example, 1 g / m 2 More than 10g / m 2 Less than 1 g / m 2 More than 5g / m 2 The following is the result.
[0087] (Heat-resistant resin layer) The laminate including the first substrate and the gas barrier resin layer may have a heat-resistant resin layer between the first substrate and the second substrate. The heat-resistant resin layer is a coating layer of a coating agent having heat resistance (hereinafter, may be simply referred to as a heat-resistant coating agent). As the heat-resistant coating agent, commercially available products can be used, such as SUNSYS FS241 manufactured by Sun Chemical Co., DH-004 / DH-HARDENER P-60 manufactured by DIC Corporation, and Michelman Co.
[0088] Also preferred are heat-resistant coating agents containing compounds having a cellulose skeleton, a benzene ring skeleton, an isocyanuric ring skeleton, or an alicyclic skeleton, whose homopolymer has a glass transition temperature (hereinafter sometimes referred to as Tg) of 100° C. or higher. Specifically, for example, cellulose derivatives such as cellulose nitrate, cellulose acetate, cellulose propionate, and cellulose butyrate, benzene rings such as phthalic acid, naphthalene dicarboxylic acid, and ethylene oxide (hereinafter sometimes referred to as EO) adducts of bisphenol A, and / or polyester resins having alicyclic skeletons such as cyclopentanediol and dimethyloltricyclodecane, or aromatic isocyanates such as diphenylmethane diisocyanate, toluene diisocyanate, xylene diisocyanate, and naphthalene diisocyanate, alicyclic isocyanates such as isophorone diisocyanate and norbornene diisocyanate, and / or urethane resins in which isocyanuric triisocyanate is bonded to a polyol and / or tris(2-hydroxyethyl)isocyanurate may be mentioned. Also, polyisocyanates using the above-mentioned isocyanates may be used as a curing agent. Also preferably usable are compounds having a benzene ring and an unsaturated double bond, such as styrene and phenoxydiethylene glycol acrylate, and / or compounds having an alicyclic structure and an unsaturated double bond, such as isobornyl acrylate and dicyclopentanyl acrylate, and radical copolymers of (meth)acrylate, etc. Also, in consideration of adhesion to olefin films, a resin with a low Tg may be mixed and used. The total content of the cellulose skeleton, benzene ring skeleton, isocyanuric ring skeleton and alicyclic skeleton of the above-mentioned compound is preferably 20 to 90% by mass, and more preferably 30 to 80% by mass, of the solid content of the heat-resistant coating layer (A).
[0089] The heat-resistant coating agent may be colored. The colorant is not particularly limited, and examples thereof include inorganic pigments, organic pigments, and dyes used in general inks, paints, and recording agents, such as those used in the printing layer (E) described below. Among these, pigments are preferred. Examples of organic pigments include soluble azo-based, insoluble azo-based, azo-based, phthalocyanine-based, halogenated phthalocyanine-based, anthraquinone-based, anthanthrone-based, dianthraquinonyl-based, anthrapyrimidine-based, perylene-based, perinone-based, quinacridone-based, thioindigo-based, dioxazine-based, isoindolinone-based, quinophthalone-based, azomethine azo-based, flavanthrone-based, diketopyrrolopyrrole-based, isoindoline-based, indanthrone-based, and carbon black-based pigments. Other examples include carmine 6B, lake red C, permanent red 2B, disazo yellow, pyrazolone orange, carmine FB, chromophthalic yellow, chromophthalic red, phthalocyanine blue, phthalocyanine green, dioxazine violet, quinacridone magenta, quinacridone red, indanthrone blue, pyrimidine yellow, thioindigo bordeaux, thioindigo magenta, perylene red, perinone orange, isoindolinone yellow, aniline black, diketopyrrolopyrrole red, daylight fluorescent pigments, etc. In addition, both non-acid-treated pigments and acid-treated pigments can be used.
[0090] Examples of inorganic pigments include white inorganic pigments such as titanium oxide, zinc oxide, zinc sulfide, barium sulfate, calcium carbonate, chromium oxide, silica, litbones, antimony white, and gypsum. Among inorganic pigments, titanium oxide is particularly preferred. Titanium oxide is white and is preferred in terms of coloring power, hiding power, chemical resistance, and weather resistance, and from the viewpoint of printing performance, the titanium oxide is preferably treated with silica and / or alumina. Examples of inorganic pigments other than white include aluminum particles, mica, bronze powder, chrome vermilion, yellow lead, cadmium yellow, cadmium red, ultramarine, Prussian blue, red iron oxide, yellow iron oxide, and zircon. Aluminum is in powder or paste form, but it is preferable to use it in paste form from the standpoint of handleability and safety. Whether leafing or non-leafing aluminum is used is appropriately selected from the standpoint of brightness and concentration.
[0091] In addition, the heat-resistant coating agent preferably uses inorganic fine particles such as alumina, magnesia, titania, zirconia, and silica (quartz, fumed silica, precipitated silica, silicic anhydride, fused silica, crystalline silica, and ultrafine amorphous silica) as aggregates because they have excellent heat resistance. Alternatively, boron nitride, aluminum nitride, alumina oxide, titanium oxide, magnesium oxide, zinc oxide, and silicon oxide are preferable because they have excellent thermal conductivity. The inorganic fine particles may be used alone or in combination. The shape of the silica fine particles is not particularly limited, and spherical, hollow, porous, rod-like, plate-like, fibrous, or amorphous silica fine particles can be used. For example, commercially available hollow silica fine particles include Silinax manufactured by Nittetsu Mining Co., Ltd.
[0092] The primary particle diameter of the inorganic fine particles is preferably in the range of 5 to 200 nm. If it is 5 nm or more, the inorganic fine particles in the dispersion are well dispersed, and if it is within 200 nm, the strength of the cured product is good. It is more preferably 10 nm to 100 nm. The inorganic fine particles can be mixed in a ratio of 5 to 90% by weight based on the total solid content of the heat-resistant coating agent and the inorganic fine particles, and the amount may be changed as appropriate depending on the purpose. In particular, the amount is preferably 20% by weight or more.
[0093] The heat-resistant coating agent may contain wax, silicon additives, or organic beads to prevent damage to the coating film, prevent blocking during laminate formation, and impart processability during bag making after the laminate is formed. Specifically, waxes such as amide wax, polypropylene wax, polyethylene wax, paraffin wax, carnauba wax, and rice wax, ethylene oxide (EO) adducts of dimethylsiloxane, silicon additives of silicon modifications, and organic beads made of acrylic, nylon, urethane, or epoxy may be added.
[0094] The solvent used in the heat-resistant coating agent is not particularly limited, and examples thereof include water, aromatic hydrocarbon organic solvents such as toluene, xylene, Solvesso #100, Solvesso #150, etc., aliphatic hydrocarbon organic solvents such as hexane, methylcyclohexane, heptane, octane, decane, etc., and various ester-based organic solvents such as methyl acetate, ethyl acetate, isopropyl acetate, normal propyl acetate, butyl acetate, amyl acetate, ethyl formate, butyl propionate, etc. Examples of water-miscible organic solvents include alcohols such as methanol, ethanol, propanol, butanol, and isopropyl alcohol, ketones such as acetone, methyl ethyl ketone, and cyclohexanone, and glycol ethers such as ethylene glycol (mono, di) methyl ether, ethylene glycol (mono, di) ethyl ether, ethylene glycol monopropyl ether, ethylene glycol monoisopropyl ether, monobutyl ether, diethylene glycol (mono, di) methyl ether, diethylene glycol (mono, di) ethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monobutyl ether, triethylene glycol (mono, di) methyl ether, propylene glycol (mono, di) methyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, and dipropylene glycol (mono, di) methyl ether. These can be used alone or in combination of two or more. In order to perform coating more effectively, a defoamer or a leveling agent may be used.
[0095] The coating amount of the heat-resistant resin layer is appropriately selected depending on the application, but the coating amount after drying is preferably 0.01 to 100 g / m 2 is preferable, and 0.1 to 50 g / m 2 More preferably, 0.5 to 3 g / m 2 is particularly preferred.
[0096] (Laminated structure) An example of a specific embodiment of the laminate of the present invention will be given below, although it is needless to say that the laminate of the present invention is not limited to this embodiment. First substrate / gas barrier resin layer / gas barrier adhesive layer / second substrate First substrate / printed layer / gas barrier resin layer / gas barrier adhesive layer / second substrate Printing layer / first substrate / gas barrier resin layer / gas barrier adhesive layer / second substrate First substrate / gas barrier resin layer / gas barrier adhesive layer / substrate used as intermediate layer / adhesive layer / second substrate First substrate / printing layer / gas barrier resin layer / gas barrier adhesive layer / substrate used as intermediate layer / adhesive layer / second substrate Printing layer / first substrate / gas barrier resin layer / gas barrier adhesive layer / substrate used as intermediate layer / adhesive layer / second substrate First substrate / gas barrier resin layer / gas barrier adhesive layer / second substrate First substrate / printed layer / gas barrier resin layer / gas barrier adhesive layer / second substrate Printing layer / first substrate / gas barrier resin layer / gas barrier adhesive layer / second substrate First substrate / gas barrier resin layer / gas barrier adhesive layer / substrate used as intermediate layer / adhesive layer / second substrate First substrate / printing layer / gas barrier resin layer / gas barrier adhesive layer / substrate used as intermediate layer / adhesive layer / second substrate Printing layer / first substrate / gas barrier resin layer / gas barrier adhesive layer / substrate used as intermediate layer / adhesive layer / second substrate
[0097] Heat-resistant resin layer / first substrate / gas barrier resin layer / gas barrier adhesive layer / second substrate Heat-resistant resin layer / first substrate / printing layer / gas barrier resin layer / gas barrier adhesive layer / second substrate Heat-resistant resin layer / printing layer / first substrate / gas barrier resin layer / gas barrier adhesive layer / second substrate Heat-resistant resin layer / first substrate / gas barrier resin layer / gas barrier adhesive layer / substrate used as intermediate layer / adhesive layer / second substrate Heat-resistant resin layer / first substrate / printing layer / gas barrier resin layer / gas barrier adhesive layer / substrate used as intermediate layer / adhesive layer / second substrate Heat-resistant resin layer / printing layer / first substrate / gas barrier resin layer / gas barrier adhesive layer / substrate used as intermediate layer / adhesive layer / second substrate
[0098] Heat-resistant resin layer / first substrate / gas barrier adhesive layer / second substrate Heat-resistant resin layer / first substrate / printed layer / gas barrier adhesive layer / second substrate Heat-resistant resin layer / printed layer / first substrate / gas barrier adhesive layer / second substrate Furthermore, the first substrate may have a coating layer on it to impart functions such as release properties and antistatic properties.
[0099] (packaging material) The laminate of the present invention can be used as a multi-layer packaging material for protecting foods, medicines, etc. When used as a multi-layer packaging material, the layer structure can be changed depending on the contents, the environment of use, and the form of use. In addition, the package of the present invention may be appropriately provided with an easy-opening treatment or a resealable means.
[0100] Taking a laminate having a sealant layer as an example of the packaging material of the present invention, the laminate is laminated with the sealant layer facing each other, and then the peripheral edge is heat-sealed to form a bag. Examples of the bag-making method include folding or overlapping the laminate of the present invention so that the inner layer surface (sealant layer surface) faces each other, and heat-sealing the peripheral edge, for example, by a side seal type, a two-sided seal type, a three-sided seal type, a four-sided seal type, an envelope seal type, a grooving seal type, a pleated seal type, a flat bottom seal type, a square bottom seal type, a gusset type, or other heat seal type. The packaging material of the present invention can take various forms depending on the contents, the environment of use, and the form of use. Self-supporting packaging materials (standing pouches) are also possible. Heat sealing can be performed by known methods such as bar seal, rotary roll seal, belt seal, impulse seal, high frequency seal, and ultrasonic seal.
[0101] In the case where the first substrate and the second substrate of the laminate of the present invention do not function as a sealant layer that serves as a heat-sealing site when forming a packaging material, a sealant layer may be further added. The sealant layer may be an additional substrate bonded with the adhesive of the present invention, or may be an adhesive layer made of the adhesive of the present invention.
[0102] The packaging material of the present invention is filled with contents through its opening, and the opening is then heat-sealed to produce a product using the packaging material of the present invention. The contents to be filled include, for example, foods such as rice crackers, bean snacks, nuts, biscuits, cookies, wafers, marshmallows, pies, semi-dried cakes, candies, snacks, and other confectioneries, bread, snack noodles, instant noodles, dried noodles, pasta, aseptically packaged cooked rice, porridge, porridge, packaged rice cakes, and cereal foods, and other staple foods, pickles, boiled beans, natto, miso, frozen tofu, tofu, nametake mushrooms, konjac, wild vegetable processed products, jams, peanut cream, salads, frozen vegetables, and potato processed products, livestock processed products such as hams, bacon, sausages, chicken processed products, and corned beef, and fish hams, These include processed seafood products such as sausages, fish paste products, kamaboko, nori, tsukudani, bonito flakes, shiokara, smoked salmon, and spicy cod roe; fruit pulp such as peaches, mandarin oranges, pineapples, apples, pears, and cherries; vegetables such as corn, asparagus, mushrooms, onions, carrots, radishes, and potatoes; cooked foods such as hamburger steaks, meatballs, seafood fries, gyoza, croquettes, and other frozen and chilled prepared foods; dairy products such as butter, margarine, cheese, cream, instant creamy powder, and infant formula; liquid seasonings, retort curry, and pet food.
[0103] In addition, the composition can be used as a packaging material for various non-food items, such as tobacco, disposable hand warmers, medicines such as infusion packs, liquid laundry detergent, liquid kitchen detergent, liquid bath detergent, liquid bath soap, liquid shampoo, liquid conditioner, cosmetics such as lotion and milky lotion, vacuum insulation materials, batteries, etc. EXAMPLES
[0104] The present invention will be described in more detail below with reference to specific synthesis examples and examples, but the present invention is not limited to these examples. In the following examples, "parts" and "%" respectively represent "parts by mass" and "% by mass" unless otherwise specified.
[0105] <Production of the first substrate> [Production Example 1] A PET film with a thickness of 12 μm was prepared as the first substrate. The surface of the PET film on which the inorganic oxide deposition layer was to be formed was subjected to plasma pretreatment, and then an aluminum oxide deposition film with a thickness of 15 nm was formed on the plasma-treated surface by reactive resistance heating as the heating means for the vacuum deposition method under the following conditions. This film was called AlOxPET. (Aluminum oxide deposition conditions): Vacuum degree: 8.1 x 10 -2 Pa
[0106] [Production Example 2] A 16 μm thick OPP film was prepared as the first substrate. An aluminum oxide vapor deposition film with a thickness of 15 nm was formed on the OPP film under the same conditions as in Production Example 1. This film was called AlOxOPP.
[0107] [Production Example 3] A 40 μm thick OPE film was prepared as a film to be used as a first substrate. An aluminum oxide vapor deposition film having a thickness of 15 nm was formed on the OPE film under the same conditions as in Production Example 1. This film was called AlOxOPE.
[0108] <Production of Gas Barrier Resin Layer A1> [Production Example 4] According to the composition shown in Table 1, a hydrolyzed liquid of composition (Y) prepared in advance was added to a mixed liquid of composition (X) prepared, and the mixture was stirred to obtain a colorless and transparent gas barrier resin solution C1.
[0109] [Table 1]
[0110] <Production of Gas Barrier Resin Layer A2> [Production Example 5] In a flask, 30 g of polyacrylic acid (hereinafter sometimes abbreviated as PAA) with a molecular weight of 200,000 (Toagosei Co., Ltd., Aron A-10H) was dissolved in isopropyl alcohol (hereinafter sometimes abbreviated as IPA) while stirring and boiling to obtain a PAA solution with a solid content of 3%. To 100 g of this solution, 5 g of a concentrated phosphoric acid IPA solution with a solid content of 5% was added by diluting a solution of concentrated phosphoric acid (Tokyo Chemical Industry Co., Ltd., solid content 86%) with IPA to obtain a gas barrier resin solution C2.
[0111] [Production Example 6] 300g of zinc oxide (hereinafter sometimes abbreviated as ZnO) with a primary particle size of 200nm (manufactured by Sakai Chemical Industry Co., Ltd., FINEX-50) and 700g of methyl ethyl ketone (hereinafter sometimes abbreviated as MEK) were mixed and dispersed for 1 hour in a bead mill (Kotobuki Chemical Co., Ltd., Ultra Aspek Mill UAM-015) using zirconia beads with a diameter of 0.3mm, and the beads were then sieved to obtain a ZnO solution with a solid content concentration of 30%. The primary particle size of ZnO in this dispersion was 88nm. This solution was mixed and stirred with a polyester resin (product name: Vylon 500, manufactured by Toyobo Co., Ltd.) solution with a solid content of 5% dissolved in MEK and an MEK solution to obtain a ZnO dispersion. The mixing ratio was ZnO solution: 20g, polyester resin solution: 20g, MEK: 60g. Polyester resin, MEK solution, and a stirrer were placed in a 200 ml beaker, and the stirrer was rotated at 200 rpm. After confirming that the polyester resin and MEK were homogenized, the ZnO solution was added to obtain a ZnO dispersion. The solid content was 7%. The resulting gas barrier resin solution was called C3.
[0112] [Production Example 7] <Production of heat-resistant resin layer> A composition consisting of 100 parts of CAP-504-0.2 (cellulose acetate propionate manufactured by Eastman Chemical Co.) and 21 parts of KW-75 (aromatic polyisocyanate manufactured by DIC Corporation) was diluted to a coating weight of 1.0 to 2.0 g / m2 when dried. 2 The obtained heat-resistant resin coating material is called C4.
[0113] [Example 1] AlOxPET / gas barrier resin layer C1 / gas barrier adhesive layer / CPP The gas barrier resin solution C1 prepared above was coated onto AlOxPET by the direct gravure method. It was then heated at 85°C for 60 seconds to form a gas barrier resin layer with a thickness of 300 nm (in a dry state). Next, a non-axially oriented polypropylene film (CPP, thickness 30 μm) was laminated onto the barrier coat layer of the barrier film obtained above via an adhesive (PASLIM VM001 / VM108CP, manufactured by DIC Corporation) having oxygen barrier properties.
[0114] [Example 2] AlOxPET / gas barrier resin layer C1 / gas barrier adhesive layer / nylon / adhesive layer / CPP A nylon film (thickness 25 μm) was laminated on the barrier resin layer obtained in the process of Example 1 via an adhesive having oxygen barrier properties (PASLIM VM001 / VM108CP, manufactured by DIC Corporation). A CPP film (thickness 70 μm) was laminated on the uncoated surface of the nylon film of the obtained laminate via an adhesive having no oxygen barrier properties (Takelac A520 / Takenate A 50, manufactured by Mitsui Chemicals, Inc.).
[0115] [Example 3] AlOxPET / gas barrier resin layer C2 / gas barrier resin layer C3 / gas barrier adhesive layer / CPP The gas barrier resin solution C2 prepared above was applied to AlOxPET and dried in the same manner as in Example 1, and then the gas barrier resin solution C3 was applied and dried in the same manner as in Example 1. A CPP film (thickness 30 μm) was laminated on the coated surface of the obtained laminate via an adhesive having oxygen barrier properties (PASLIM VM001 / VM108CP, manufactured by DIC Corporation).
[0116] [Example 4] AlOxPET / gas barrier resin layer C2 / gas barrier resin layer C3 / gas barrier adhesive layer / nylon / adhesive layer / CPP A laminate was obtained in the same manner as in Example 2, except that the gas barrier resin layer C1 in Example 2 was changed to a gas barrier resin layer C2 / gas barrier resin layer C3.
[0117] [Example 5] AlOxOPP / gas barrier resin layer C1 / gas barrier adhesive layer / CPP A laminate was obtained in the same manner as in Example 1, except that the AlOxPET in Example 1 was changed to AlOxOPP.
[0118] [Example 6] AlOxOPP / gas barrier resin layer C1 / gas barrier adhesive layer / OPP / adhesive layer / CPP A laminate was obtained in the same manner as in Example 2, except that the AlOxPET in Example 2 was changed to AlOxOPP and the nylon film was changed to an OPP film (thickness: 20 μm).
[0119] [Example 7] AlOxOPP / gas barrier resin layer C2 / gas barrier resin layer C3 / gas barrier adhesive layer / CPP A laminate was obtained in the same manner as in Example 3, except that the AlOxPET in Example 3 was changed to AlOxOPP.
[0120] [Example 8] AlOxOPP / gas barrier resin layer C2 / gas barrier resin layer C3 / gas barrier adhesive layer / OPP / adhesive layer / CPP A laminate was obtained in the same manner as in Example 4, except that the AlOxPET in Example 4 was changed to AlOxOPP and the nylon film was changed to an OPP film (thickness: 20 μm).
[0121] [Example 9] AlOxOPE / Gas barrier adhesive layer / LLDPE An LLDPE film (thickness 60 μm) was laminated onto AlOxOPE via an adhesive with oxygen barrier properties (PASLIM VM001 / VM108CP, manufactured by DIC Corporation).
[0122] [Example 10] Heat-resistant resin layer C4 / AlOxOPE / Gas barrier adhesive layer / LLDPE A heat-resistant resin coating material C4 was applied to AlOxOPE, and an adhesive with oxygen barrier properties (PASLIM VM001 / VM108CP, manufactured by DIC Corporation) was applied to the side that was not coated with the coating material, and an LLDPE film (thickness 60 μm) was laminated on it.
[0123] [Example 11] Heat-resistant resin layer C4 / AlOxOPE / Gas barrier resin layer C1 / Gas barrier adhesive layer / LLDPE A heat-resistant resin coating material C4 was applied to AlOxOPE, and the gas barrier resin solution C1 was applied to the surface not coated with the coating material and dried in the same manner as in Example 1. Furthermore, an adhesive having oxygen barrier properties (PASLIM VM001 / VM108CP, manufactured by DIC Corporation) was applied onto the obtained gas barrier resin layer, and an LLDPE film (thickness 60 μm) was laminated thereon.
[0124] [Example 12] Heat-resistant resin layer C4 / AlOxOPE / gas barrier resin layer C2 / gas barrier resin layer C3 / gas barrier adhesive layer / LLDPE The heat-resistant resin coating material C4 was applied to AlOxOPE, and the gas barrier resin solutions C2 and C3 were applied to the surface not coated with the coating material and dried in the same manner as in Example 3. Furthermore, an adhesive having oxygen barrier properties (PASLIM VM001 / VM108CP, manufactured by DIC Corporation) was applied onto the obtained gas barrier resin layer, and an LLDPE film (thickness 60 μm) was laminated thereon.
[0125] [Comparative Example 1] The barrier resin layer in Example 1 was changed to a polyester resin (Vylon 500, Toyobo Co., Ltd.) that does not have barrier properties, and a coating layer was formed by coating and drying in the same manner. The adhesive with oxygen barrier properties was changed to an adhesive without oxygen barrier properties (Takelac A520 / Takenate A 50 (Mitsui Chemicals Co., Ltd.)), and a CPP film (thickness 30 μm) was laminated.
[0126] [Comparative Example 2] The barrier resin layer of Example 2 was changed to a polyester resin (Vylon 500, Toyobo Co., Ltd.) that does not have barrier properties, and the resin was coated and dried in the same manner to form a coating layer. The adhesive with oxygen barrier properties was changed to an adhesive without oxygen barrier properties (Takelac A520 / Takenate A 50 (Mitsui Chemicals Co., Ltd.)), and a CPP film (thickness 70 μm) was laminated.
[0127] [Comparative Example 3] A laminate was obtained in the same manner as in Comparative Example 1, except that the AlOxPET in Comparative Example 1 was changed to AlOxOPP.
[0128] [Comparative Example 4] A laminate was obtained in the same manner as in Comparative Example 2, except that the AlOxPET in Comparative Example 2 was changed to AlOxOPP and the nylon film was changed to an OPP film (thickness: 20 μm).
[0129] [Comparative Example 5] The adhesive having oxygen barrier properties in Example 9 was changed to an adhesive having no oxygen barrier properties (Takelac A520 / Takenate A 50 (Mitsui Chemicals, Inc.)), and an LLDPE film (thickness 60 μm) was laminated.
[0130] [Comparative Example 6] The adhesive having oxygen barrier properties in Example 10 was changed to an adhesive having no oxygen barrier properties (Takelac A520 / Takenate A 50 (Mitsui Chemicals, Inc.)), and an LLDPE film (thickness 60 μm) was laminated.
[0131] [Comparative Example 7] The barrier resin layer of Example 11 was changed to a polyester resin (Vylon 500, Toyobo Co., Ltd.) that does not have barrier properties, and the resin was coated and dried in the same manner to form a coating layer. The adhesive with oxygen barrier properties was changed to an adhesive without oxygen barrier properties (Takelac A520 / Takenate A 50 (Mitsui Chemicals Co., Ltd.)), and an LLDPE film (thickness 60 μm) was laminated.
[0132] (Oxygen permeability measurement) The laminates produced in the above examples and comparative examples were measured for oxygen permeability (cc / m) in accordance with JIS K7126 using an oxygen permeability measuring device (manufactured by MOCON, Inc. (model name: OX-TRAN 2 / 21)) set so that the oxygen supply side was the substrate layer surface of the barrier film under measurement conditions of 23°C and 90% RH atmosphere. 2 The measurement results are shown in Tables 2, 3, and 4.
[0133] (Measurement of water vapor permeability) The laminates produced in the above examples and comparative examples were measured for water vapor transmission rate (g / m2) in accordance with JIS K7129 using a water vapor transmission rate measuring device (MOCON, model name: PERMATRAN 3 / 33)) set so that the sensor side was the substrate layer side of the barrier film under measurement conditions of 40°C and 100% RH atmosphere. 2 The results are shown in Tables 2, 3, and 4.
[0134] <Performance evaluation of laminate> The packaging materials produced in the above examples and comparative examples were formed into a cylindrical shape and the Gelbo Flex test in accordance with ASTM F392 was repeated five times. After that, a part of the packaging material was cut out to obtain a test sample, and the oxygen permeability and water vapor permeability were measured. The following measurement results are the average values of three samples. Table 2 shows the evaluation of the laminate using AlOxPET. Table 3 shows the evaluation of the laminate using AlOxOPP. Table 4 shows the evaluation of the laminate using AlOxOPE.
[0135] [Table 2]
[0136] The results in Table 2 above show that the laminate having AlOxPET, a gas barrier resin layer, and an oxygen barrier adhesive layer exhibited excellent oxygen barrier properties even in its normal state, and showed little deterioration in gas barrier properties even after the Gelbo flex test, as well as excellent flex resistance.
[0137] [Table 3]
[0138] The results in Table 3 above show that the laminate having AlOxOPP, a gas barrier resin layer, and an oxygen barrier adhesive layer exhibited excellent oxygen barrier properties even in its normal state, and showed little deterioration in gas barrier properties even after the Gelbo flex test, as well as excellent flex resistance.
[0139] [Table 4]
[0140] The results in Table 4 above show that the laminate having a heat-resistant resin layer, AlOxOPE, a gas barrier resin layer, and an oxygen barrier adhesive layer exhibited excellent oxygen barrier properties even in normal conditions, and showed little deterioration in gas barrier properties even after the Gelbo flex test, as well as excellent flex resistance.
Claims
1. A laminate including a first substrate and a gas barrier resin layer, The gas barrier resin layer is (A1) or (A2). (1) A water-soluble polymer having a hydroxyl group and Si(OR 1 ) 4 , or R 2 Si(OR 3 ) 3 (However, OR 1 and OR 3 represents a hydrolyzable group, R 2 represents an organic functional group), or one or more hydrolyzates of the silicon compounds. (2) Gas barrier resin layer (A2) containing a dehydrating condensable heteroatom compound and a polymer having a carboxyl group
2. The laminate according to claim 1 , comprising the first substrate, the gas barrier resin layer, a gas barrier adhesive layer, and a second substrate.
3. The laminate according to claim 1 , comprising a heat-resistant resin layer, the first substrate, the gas barrier resin layer, and a second substrate.
4. The laminate according to claim 1 , wherein the first substrate is an olefin-based resin substrate.
5. The laminate according to claim 2 , wherein the first substrate and the second substrate are olefin-based resin substrates.
6. A packaging material comprising the laminate according to any one of claims 1 to 5.
Citation Information
Patent Citations
Optical filter using gas barrier type film and organic el display
JP2005077553A
Transparent gas barrier film
JP2010253861A